2018
DOI: 10.1038/s41372-018-0150-7
|View full text |Cite
|
Sign up to set email alerts
|

Plasma proteome changes in cord blood samples from preterm infants

Abstract: Plasma proteome analysis revealed numerous gestation-age-dependent protein abundance differences between term and preterm infants, which highlight key dysregulated pathways and potential new protein treatment targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 71 publications
1
15
0
Order By: Relevance
“…The plasma proteome for adults and infants [24] has been previously described, but, to our knowledge, we provide the first comparison of infant plasma and lung fluid protein profile and evidence for the close proportional abundance in the two tissue compartments. This finding indicates that most plasma proteins, irrespective of their size, pass the endothelial/epithelial barrier and accumulate in lung fluid in the injured infant lung similar to the observation in adults with acute respiratory distress syndrome [25].…”
Section: Plos Onementioning
confidence: 81%
“…The plasma proteome for adults and infants [24] has been previously described, but, to our knowledge, we provide the first comparison of infant plasma and lung fluid protein profile and evidence for the close proportional abundance in the two tissue compartments. This finding indicates that most plasma proteins, irrespective of their size, pass the endothelial/epithelial barrier and accumulate in lung fluid in the injured infant lung similar to the observation in adults with acute respiratory distress syndrome [25].…”
Section: Plos Onementioning
confidence: 81%
“…Suski et al completed several studies [ 13 , 14 ] investigating plasma proteome changes in preterm infants comparing gestational ages [ 13 ] and malfunctioning proteins in various signalling pathways [ 14 ]. Utilising a tandem MS approach they were able to identify proteomic changes across varying gestational ages for several pathways which include; coagulation, inflammation, complement activations and immunomodulation [ 13 , 14 ]. Suski et al also observed Complement C3, Factor V and Complement C4-A were associated with gestational age [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…A formal sample size calculation was not performed so as to allow the realization of a hypothesis generating study. The approximate sample size was based on the calculations for the main study [7]. Briefly, the basic goal of the main project was to compare protein abundance levels between groups with a different degree of maturity.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous publications, we described the comparison between abundances of all plasma proteins from prematurely born children with different gestational ages, both from cord blood as well as at the 36th postmenstrual week (36 PMA) [79]. The articles presented that proteome differences are highly gestational age-dependent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation